2023
DOI: 10.3390/fermentation9020196
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Hydrocarbon Catabolic Pathways as Targets for Metabolic Engineering Strategies for Enhanced Bioremediation of Crude-Oil-Contaminated Environments

Abstract: Anthropogenic activities and industrial effluents are the major sources of petroleum hydrocarbon contamination in different environments. Microbe-based remediation techniques are known to be effective, inexpensive, and environmentally safe. In this review, the metabolic-target-specific pathway engineering processes used for improving the bioremediation of hydrocarbon-contaminated environments have been described. The microbiomes are characterised using environmental genomics approaches that can provide a means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 223 publications
0
4
0
Order By: Relevance
“…The total crude oil hydrocarbon-utilizing bacteria and fungi counts obtained from the present study were significantly lower than those reported by Udomessien et al [27] who worked with polluted water samples from the Iko River situated within the petroleum belt of the Niger Delta, Nigeria, but were relatively similar to those in the study of Ogbonna et al [28] who carried out an analysis of water samples from crude oil-impacted surface water in Bodo/Bonny River, Nigeria. As shown in Table 1, the ability to isolate elevated numbers of certain oil-degrading microorganisms from the crude oil-polluted environment is often taken as proof that these microorganisms are the vigorous degraders of that environment, with the crude oil tolerance test and Gas Chromatography-Mass Spectrometry (GC-MS) confirming the ability of these microorganisms to degrade or utilize crude oil hydrocarbons [29,30]. In the recent past, the applications of microbes to deal with environmental pollutants have become an auspicious technology because of its economical and eco-friendly nature [31].…”
Section: Discussionmentioning
confidence: 99%
“…The total crude oil hydrocarbon-utilizing bacteria and fungi counts obtained from the present study were significantly lower than those reported by Udomessien et al [27] who worked with polluted water samples from the Iko River situated within the petroleum belt of the Niger Delta, Nigeria, but were relatively similar to those in the study of Ogbonna et al [28] who carried out an analysis of water samples from crude oil-impacted surface water in Bodo/Bonny River, Nigeria. As shown in Table 1, the ability to isolate elevated numbers of certain oil-degrading microorganisms from the crude oil-polluted environment is often taken as proof that these microorganisms are the vigorous degraders of that environment, with the crude oil tolerance test and Gas Chromatography-Mass Spectrometry (GC-MS) confirming the ability of these microorganisms to degrade or utilize crude oil hydrocarbons [29,30]. In the recent past, the applications of microbes to deal with environmental pollutants have become an auspicious technology because of its economical and eco-friendly nature [31].…”
Section: Discussionmentioning
confidence: 99%
“…The development of consortia of engineered microbes that can synergistically degrade different types of plastics while simultaneously producing biogas is a particularly promising area of research. Furthermore, the application of CRISPR-Cas systems for the targeted enhancement of microbial tolerance to MP-associated stressors could lead to more robust microbial consortia in anaerobic digesters [95]. Through the application of cutting-edge genetic engineering, particularly CRISPR-Cas genome editing, scientists are optimizing acetogens like Clostridium ljungdahlii for superior biogas production by enhancing their C1 gas conversion capabilities, with systems like AlphaFold2 aiding in the meticulous design of the Wood-Ljungdahl pathway enzymes to transform emissions into value-added biochemicals sustainably [96].…”
Section: Advancements In Microbial Engineering Techniquesmentioning
confidence: 99%
“…Metabolic pathway reconstruction is widely used in the degradation of environmental pollutants such as crude oil, microplastics, pesticides, etc. ; therefore, its proper application in waste to energy strategy will be very promising [213]. In recent times, the field of genetic engineering has seen the emergence of new genome-editing tools, such as CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats-associated protein Cas9), TALEN (transcription activator-like effector nucleases), and ZFN (zinc-finger nucleases).…”
Section: Microbe-based Large-scale Commercial Biogas Plantsmentioning
confidence: 99%
“…These tools provide efficient means of modifying genes in microorganisms. These tools allow for targeted activation or suppression of specific gene expressions, enabling researchers to precisely manipulate the genetic makeup of microorganisms involved in any specific process [213]. The utilization of these gene-interfering tools holds significant potential in enhancing the efficiency and performance of microorganisms for biogas production.…”
Section: Microbe-based Large-scale Commercial Biogas Plantsmentioning
confidence: 99%